Gallant by Bold: final year degree online exhibition bachelor of Graphic Design class of 2021: advertising / Fakulti Seni Lukis & Seni Reka UiTM Shah Alam - Universiti Teknologi MARA, Fakulti Seni Lukis & Seni Reka (Fakulti Seni Lukis & Seni Reka UiTM Shah Alam, 2021)
Advertising is the act of calling public attention to one's product, service, and need It is a means of communication with the purpose of persuading the public to respond in a certain way toward what is advertised.